Batas Kualitas Langit yang Ideal untuk Lokasi Observasi Awal Waktu Subuh - Damanhuri, Adi; Solikin, Agus (University of Muhammadiyah Sumatera Utara, 2022)
This article describes the ideal sky quality limit to be used as an early subuh prayer time observation location, considering that early subuh prayer time research using a Sky Quality Meter (SQM) is mostly carried out from various observation locations with different sky quality. The research method used is quantitative with a sample of 6 observation locations with a daily data amount of 945. The data analysis carried out is to find a correlation between the night level which represents the quality of the sky and the inflection point which represents the sign of the appearance of the early subuh prayer time. Based on the analysis, it is concluded that the ideal sky quality limit to be used as a location for observing early subuh prayer time data using SQM is 20.35 mpsas. This limit is an important consideration for all parties who will conduct observations at early subuh prayer time, must choose locations that have a minimum night level of 20.35 mpsas.